2021
DOI: 10.1364/boe.412769
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric property measurements of corneal tissues for computational dosimetry of the eye in terahertz band in vivo and in vitro

Abstract: The dielectric constant of the normal corneal tissue of a rabbit eye was obtained in vitro in the range from approximately 0.1 to 1 THz, and the drying process on the eye surface exposed to high-power terahertz waves was investigated by in vivo reflectance measurement using terahertz time-domain spectroscopy. When the rabbit eye was exposed to terahertz waves at 162 GHz for 6 min with an irradiation power of 360 or 480 mW/cm2, the reflectance temporally increased and then decreased with a temperature increase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In addition, THz waves have been shown to not affect corneal tissue [37]. Other studies have demonstrated the sensitivity of the terahertz dielectric response to water content changes in ex vivo [38,39] and in vivo corneal samples [40][41][42]. In addition, we have presented a finite-difference time-domain method for modeling the THz response to tissue hydration changes.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, THz waves have been shown to not affect corneal tissue [37]. Other studies have demonstrated the sensitivity of the terahertz dielectric response to water content changes in ex vivo [38,39] and in vivo corneal samples [40][41][42]. In addition, we have presented a finite-difference time-domain method for modeling the THz response to tissue hydration changes.…”
Section: Introductionmentioning
confidence: 95%
“…1(a) and equation (1) where ω(f) is the frequency dependent beam radius at the axicon surface, β 0 is the inclination angle of the rays defined by the external cone angle α and lens material permittivity εr as in equations ( 2) [20]. Equation (3) shows that the axially directed k-vector, k z , is less than the free space k and thus the phase velocity is superluminal [21]; υ p ~ 1.04c 0 for α = 25 o…”
Section: A Backgroundmentioning
confidence: 99%
“…THz sensing corneal tissue is an expanding research topic that has been investigated by various research groups [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…186 Mizuno et al performed a series of in vivo measurements investigating the effects of THz radiation on corneal tissues. 187,188 They irradiated the corneal tissue of each rabbit with a 162 GHz CW source with powers ranging from 60 to 600 mW cm À2 for 6 min. The corneal thickness, opacity, and temperature were measured and they also checked for corneal epithelium damage.…”
Section: Radiation Concerns and Effectsmentioning
confidence: 99%